Reformasi Hukum Tata Negara Islam melalui Pendekatan Maqasid Al-Shariah Perspektif Jasser Auda - Rini Nur Amaliah; Nirmalasari Nirmalasari; Kurniati Kurniati (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the reform of Islamic constitutional law through the Maqasid alShariah approach from the perspective of Jasser Auda. Reform of Islamic constitutional law in the contemporary era faces complex challenges related to the adaptation of sharia principles to the dynamics of modernity, democracy, and respect for human rights. The method used is a qualitative literature study to analyze classical and contemporary literature. The results of the study indicate that the existence of Islamic constitutional law is adaptive and normative, emphasizing the principles of justice, public welfare, and public participation. The mechanism for implementing constitutional law requires the application of good governance principles based on accountability, transparency, and trustworthiness. Jasser Auda's assessment of maqasid emphasizes the need for a multidimensional systemic approach, where the success of law implementation is measured by the achievement of public welfare and social justice, not merely the textual aspects of the law. This framework is expected to become a reference in the renewal of the Islamic constitutional system that is relevant to the needs of the modern state.